2017
DOI: 10.1089/dna.2017.3682
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNAMEG3Negatively Regulates Proliferation and Angiogenesis in Vascular Endothelial Cells

Abstract: Long noncoding RNA (lncRNA) MEG3 is an important tumor suppressor in several types of human cancers. However, the biological function and underlying mechanism of MEG3 in vascular endothelial cells (VECs) remain unknown. In the present study, we demonstrated the functional importance of lncRNA MEG3 in proliferation and angiogenesis of VECs. MEG3 overexpression significantly suppressed the proliferation and in vitro angiogenesis in VECs, whereas knockdown of MEG3 had the opposite effect. Furthermore, we found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(66 citation statements)
references
References 29 publications
1
65
0
Order By: Relevance
“…Many studies have indicated that the aberrant expression of lncRNAs plays an important role in several disease related to vascular endothelial cells . For example, lncRNA‐MEG3 negatively regulating miR‐9 had the function on regulating the proliferation and angiogenesis of vascular endothelial cells . LncRNA‐MALAT1 could effectively attenuate oxygen‐glucose deprivation and re‐oxygenation‐induced apoptosis of HBMECs .…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have indicated that the aberrant expression of lncRNAs plays an important role in several disease related to vascular endothelial cells . For example, lncRNA‐MEG3 negatively regulating miR‐9 had the function on regulating the proliferation and angiogenesis of vascular endothelial cells . LncRNA‐MALAT1 could effectively attenuate oxygen‐glucose deprivation and re‐oxygenation‐induced apoptosis of HBMECs .…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidences have shown that the deletion or promoter hypermethylation of the MEG3 gene promotes angiogenesis . He et al found that MEG3 suppressed the proliferation and angiogenesis of vascular endothelial cells through the interaction and suppression of miR‐9 . Angiogenesis is one of the important mechanisms for the progression of MM …”
Section: Mechanisms Of Lncrnas In MMmentioning
confidence: 99%
“…Besides, increasing MEG3 expression not only restrained proliferation but also showed a negative effect on proliferation and angiogenesis in VEC. Through further study, MEG3 exerts its tumor suppression effect by playing a miRNA sponge to regulate miR-9 [61]. These studies above suggested that MEG3 might control double effect on inhibition of CRC proliferation by impeding angiogenesis in VEC.…”
Section: The Role Of Lncrnas In Crcmentioning
confidence: 99%